Creating an entrepreneurial ecosphere within higher education institutions: towards a model of entrepreneurial university. - Ahmad, Noor Hazlina (Universiti Sains Malaysia, 2015)

(untitled)
The ASEAN countries are progressing with tremendous opportunities and scopes emphasizing on the knowledge economy. Such attempt has invigorated to find new avenues of implementing the concept of entrepreneurial university. The main purpose of the study is to distinguish the Malaysian universities which possess hard and soft elements of the entrepreneurial university. Further, the study attempted to explore the possible significant differences in context of the dimensions of entrepreneurial orientation within the entrepreneurial university paradigm.